Relevance of donor‐specific antibody monitoring after kidney transplantation: Findings from the Collaborative Transplant Study and the Heidelberg Transplant Center. (19th December 2019) - Süsal, Caner; Aykut, Güclü; Morath, Christian; Fichtner, Alexander; Unterrainer, Christian; Scherer, Sabine; Tran, Thuong H.; Mehrabi, Arianeb; Zeier, Martin; Tönshoff, Burkhard
Abstract : Monitoring of donor‐specific HLA antibodies (DSA) has become part of the clinical routine in kidney transplantation. This paper gives a brief overview on data from the Collaborative Transplant Study (CTS) and the Heidelberg Transplant Center on the clinical relevance of post‐transplant DSA monitoring in patients undergoing renal transplantation. The obtained findings underline the importance of DSA monitoring in the post‐operative course in immunologically high‐risk patients and patients with deterioration of graft function. Especially in patients with a pre‐activated immune system, a gap in the immunosuppressive therapy appear to lead to persistence, reappearance or de novo occurrence of strong, complement‐activating DSA, resulting in severe antibody‐mediated rejection (AMR) and, without timely intervention, in AMR‐related graft loss.